Performance Analysis Of Wdm Mesh Hierarchical Time Sliced Optical Burst Switched Networks (Jurnal Teknologi (Sciences & Engineering), 2012)
Although Optical Burst Switching (OBS) is seen as the favored switching technology for near–future all–optical networks, this technology still suffers from high burst drops probability as a result of contention at the buffer–less core node. Many variants of OBS have been proposed to address this issue. In this paper, the performance of a newly proposed OBS variant known as Hierarchical Time Sliced OBS (HiTSOBS) is studied. The evaluation aims at comparing the performance of HiTSOBS, in terms of burst loss probability and delay for different bandwidths in different topologies. Simulation results demonstrate that larger topologies experience higher loss and higher delay. Moreover, the simulation results show that our proposed bandwidth sharing model is good for delay sensitive applications especially at lower and medium load. Key words: Optical burst switching (OBS); hierarchical time sliced optical burst switching burst loss (HiTSOBS);, contention; burst loss probability (BLP) time slot